CONTRIBUTION OF CORPORATE SOCIAL RESPONSIBILITY AS A MEDIATOR IN FIRM VALUE - Faticha Putri, Ananda; Susilowati, Endah (Transpublika Publisher, 2024)
This research investigates the impact of Environmental, Social, Governance (ESG) and Corporate Social Responsibility (CSR) factors on the value of transportation companies listed on the Indonesia Stock Exchange. ESG and CSR have become increasingly important for businesses as stakeholders demand sustainable and socially responsible practices. The objective of this study is to comprehend how ESG and CSR affect firm value, with CSR acting as a mediator in this relationship. Additionally, the study explores the influence of Good Corporate Governance (GCG) on firm value and CSR. Quantitative methods are employed, utilizing secondary data analysis from annual reports of transportation companies listed on the Indonesia Stock Exchange. Regression techniques are used to analyze the data and test hypotheses regarding the influence of ESG, CSR, and GCG on firm value. The results indicate that ESG has a negative impact on firm value, while CSR has a positive impact. Furthermore, CSR acts as a mediator between ESG and firm value. Conversely, GCG does not significantly influence CSR or firm value. These findings suggest that transportation companies should prioritize CSR practices to enhance their firm value. Additionally, further research is needed to gain a deeper understanding of the relationship between CSR, firm value, and sustainability.